Reviving Old Scratch : demons and the devil for doubters and the disenchanted - Beck, Richard, 1967- (Theology for the people., 2016)
The devil has fallen on hard times. Surveys say that even the majority of Christians doubt his existence. And burdened by doubts skeptical believers find themselves divorced from Jesus' dramatic confrontation with Satan in the Gospels and the struggle that galvanized the witness of the early church. Reviving Old Scratch reintroduces the devil to the modern church with a biblical, bold and urgent vision of spiritual warfare where we resist the devil by joining the Kingdom of God's subversive campaign to interrupt the world with love.